AIM2 promotes non‐small‐cell lung cancer cell growth through inflammasome‐dependent pathway. Issue 11 (5th April 2019) - Zhang, Minda; Jin, Chenyu; Yang, Yunjia; Wang, Keke; Zhou, Yunjiang; Zhou, Yang; Wang, Rui; Li, Tao; Hu, Rong
Abstract: The human absent in melanoma 2 (AIM2) is considered as a DNA recognizer. AIM2 has been described as a tumor suppressor gene in the early years. But recent studies suggested that it functions as an oncogene in several cancers. However, its roles in non‐small‐cell lung cancer (NSCLC) remain unclear. Here we reported that AIM2 highly expressed in NSCLC cells and exhibited a tumor‐promoting property both in vitro and in vivo. Besides, AIM2 short hairpin RNA (shRNA)‐mediated suppression of cell proliferation was triggered by the accumulation of cells at the G2/M phase. Knockdown of AIM2 reduced the inflammasome formation, while overexpression of AIM2 or stimulation by poly(dA:dT) induced the inflammasome formation. Interestingly, blockade of the inflammasome by caspase‐1 inhibitor VX‐765 or ASC small interfering RNA (siRNA) abolished the effects brought by AIM2 shRNA and AIM2 plasmid. In summary, our results revealed that AIM2 functioned as an oncogene in NSCLC in an inflammasome‐dependent way. Abstract : Here we reported that human absent in melanoma 2 (AIM2) highly expressed in non‐small‐cell lung cancer (NSCLC) cells and exhibited a tumor‐promoting property both in vitro and in vivo. In addition, AIM2 functioned as an oncogene in NSCLC in an inflammasome‐dependent way.